2015
DOI: 10.14814/phy2.12431
|View full text |Cite
|
Sign up to set email alerts
|

High-threshold Ca2+channels behind gamma band activity in the pedunculopontine nucleus (PPN)

Abstract: The pedunculopontine nucleus (PPN) is part of the Reticular Activating System, and active during waking and REM sleep. Previous results showed that all PPN cells plateau at gamma frequencies and intrinsic membrane oscillations in PPN neurons are mediated by high-threshold N- and P/Q-type Ca2+ channels. The present study was designed to determine whether some PPN cells have only N-, only P/Q-, or both N- and P/Q-type Ca2+ channels. We used patch-clamp recordings in PPN cells in slices from anesthetized rat pups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 39 publications
7
51
0
Order By: Relevance
“…Similar results were found during recordings of voltage-dependent calcium currents. These results confirm the presence of cells in the PPN that manifest gamma band oscillations through only N-type (30%), only P/Q-type (20%), and both N- and P/Q-type (50%) calcium channels [121,122]. …”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar results were found during recordings of voltage-dependent calcium currents. These results confirm the presence of cells in the PPN that manifest gamma band oscillations through only N-type (30%), only P/Q-type (20%), and both N- and P/Q-type (50%) calcium channels [121,122]. …”
Section: Introductionsupporting
confidence: 77%
“…This new cell type classification proposes that some PPN neurons fire only during REM sleep (“REM-on”, N-type only), only during waking (“Wake-on”, P/Q-type only), or during both waking and REM sleep (“Wake/REM-on”, N-type + P/Q-type) [121,122]. Armed with this information, we could now address the role of NCS-1 and lithium in the function of gamma band activity mediated by PPN neurons.…”
Section: Introductionmentioning
confidence: 99%
“…We discovered that every PPN neuron exhibited gamma band activity via high threshold, voltage-dependent calcium channels [48]. Later, we found that ~50% of the cells have both P/Q-and N-type calcium channels, while ~25% have only one of the two channels [49]. Early studies (reviewed in [50]), had shown that PPN neurons fire in relation to states of arousal such as "Wake-REM on" cells firing during both waking and REM sleep, while others fire only during waking called "Wake on" cells, and "REM on" cells fire only during REM sleep.…”
Section: Bottom-up Gammamentioning
confidence: 97%
“…Thus, the PPTg, through each of its neuronal populations, has distinct roles in promoting waking and non-REM sleep and in modulating cortical activation and muscle tone in waking and non-REM sleep [75]. The presence of different types of high threshold calcium channels in some PPTg neurons have been proposed to modulate waking (P/Qtype), while the presence of other channels (N-type) are thought to maintain REM sleep [83,84].…”
Section: The Pptg As a Part Of The Reticular Activating System (Ras)mentioning
confidence: 99%